2014
DOI: 10.5301/jva.5000280
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Comparison of three different types of Valved and Non-Valved Peripherally inserted Central Catheters

Abstract: We found no clinical advantages of valved vs. non-valved PICCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 18 publications
0
50
3
1
Order By: Relevance
“…18 A recent study concluded that there is no significant advantage related to the presence of a proximal valve. 19 This category can be further divided into a number of catheter lumens, stepped tip versus all lumens ending at the same point, and special tip configurations that are designed to minimize thrombosis formation at the catheter tip. No studies exist that conclusively validate the efficacy of these design features.…”
Section: Cathetersmentioning
confidence: 99%
“…18 A recent study concluded that there is no significant advantage related to the presence of a proximal valve. 19 This category can be further divided into a number of catheter lumens, stepped tip versus all lumens ending at the same point, and special tip configurations that are designed to minimize thrombosis formation at the catheter tip. No studies exist that conclusively validate the efficacy of these design features.…”
Section: Cathetersmentioning
confidence: 99%
“…Improvements in polyurethane and similar components have added increased flexibility, variations in lumen size, valved and non-valved catheters and impregnation of antibiotic or anti- Fig. 3.7 Device recommendations for peripherally compatible infusions (The Michigan Appropriateness Guide for Intravenous Catheters (MAGIC) Recommendations) (Chopra et al 2015) septic components (Pittiruti et al 2014). CVADs with antimicrobial properties may be the best choice for patients with compromised immunity or a propensity for infection (Kramer et al 2017).…”
Section: Device-specific Featuresmentioning
confidence: 99%
“…Результаты исследования M. Pittiruti с соавт. позволяют сделать вывод об отсутствии разли-чий при использовании клапанных и бесклапан-ных катетеров [9]. Однако у пациента, который не вошел в данное исследование (ЦКПВ был установ-Рис.…”
Section: оригинальные статьиunclassified